Positive effect of Bifidobacterium animalis subsp. lactis VHProbi YB11 in improving gastrointestinal movement of mice having constipation - Cui, Hongchang; Wang, Qian; Feng, Congrui; Guo, Chaoqun; Zhang, Jingyan; Bu, Xinping; Duan, Zhi (Frontiers in Microbiology, 2022)
Introduction The aim of this study was to investigate the effects of Bifidobacterium animalis subsp. lactis VHProbi® YB11 (YB11) on attenuating sucralfate-induced constipation in BALB/c mice. The strain of YB11 exhibited favorable tolerance of simulated gastrointestinal (GI) juice. Only 0.42 Log value declined when the live cells of YB11 were co-incubated with simulated GI juice. Meanwhile, this strain also displayed perfect ability to adhere the intestinal epithelium Caco-2 cells with adhesion index of 18.5. 24 of female mice were randomized into four groups. Methods The normal group (NOR) was fed with a normal diet, whereas the placebo group (PLA), positive group (POS), and probiotic group (PRO) were fed with sucralfate to induce constipation. After first successfully establishing the constipation model, groups NOR and PLA received the oral administration of saline solutions. Meanwhile, the POS and PRO groups were orally administered phenolphthalein and YB11 suspensions, respectively. Several indices, including fecal water content, GI transit time, short-chain fatty acids (SCFAs), intestinal neuropeptides level, and histopathology of colonic tissues, were investigated. Results and Discussion Compared with PLA, YB11 had a positive effect in increasing the fecal water content and intestinal peristalsis. Some positive trends, including the acetic and total acids level of fecal samples, and the colonic tissue histopathology, were also observed. Furthermore, YB11 had an ability to upregulate the levels of gut excitatory neuropeptides including motilin, gastrin, and substance P, whereas it downregulated the levels of inhibitory neuropeptides including endothelin-1, somatostatin, and vasoactive intestinal peptide. We conclude that the strain YB11 has a positive impact on improving gastrointestinal mobility and reducing the severity of constipation.